Irrigation methods affect critical period of weed competition in potato production - Ghafori, Abbas.; Asgari, Ashkan.; Zahedi, Morteza.; Karimmojeni, Hassan.; Ghasemi Pirbaloti, Ahmad. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2019)
Potato (Solanum tuberosum L.) is a relatively sensitive crop to water deficit in comparison to other cultivated, it is important employing modern irrigation methods in order to meet its sufficient water requirement. The field experiment was conducted as split plots in completely random block designs in three replicationsby two tape and furrow irrigation methods in central of Iran.Experimental treatments included two series of weed-crop competition different temporal treatments in which the first series involved elimination of weed since emergence time to 20, 30, 40, 50 and 60 days after emergence and then weed presence and their competition to potato (Marphona cultivar) until season late. The second ones involved weed-crop competition since emergence to 20, 30, 40, 50 and 60 days after emergence and then weed elimination until end of season. Additionally, two control treatments involved weed-less and weed presence control during growing season were considered.Results indicated that in both irrigation methods, as interference duration increased, weed dry weight increased.Tuber yield and size reduced as weed interference period was increased.While losses in weed control interference in whole season in tape method was 90 to 95%, although in furrow method it was about 40 to 45%. Beginning of weed control critical period based on 10% acceptable yield losses as a results of weeds damage in furrow and tape irrigation methods was occurred equal to 32 days (590GDD) and 25 days (480GDD) after potato emergence respectively. End of this period in furrow and tape irrigation methods was occurred at 1190 growing day degree (GDD) equals to 59 days and 980 growing day degree (GDD) equals to 50 days after potato emergence respectively.